APLIKASI PUPUK ORGANIK CAIR (POC) KEONG MAS TERHADAP PERTUMBUHAN BIBIT KARET (Hevea brasiliensis Muell. Arg) DI MEDIA GAMBUT - Rosiana Rosiana; Sopiana Sopiana; Rika Fitry Ramanda; Ari Priyanto (Politeknik Negeri Ketapang, 2025)
Golden apple snails are pests and can be processed into liquid organic fertilizer due to their ability to improve soil quality and provide nutrients to plants. Golden apple snails contain compounds that can be used as plant nutrients, including the amino acid tryptophan, phosphorus (P), and calcium (Ca), making them suitable raw materials for liquid organic fertilizer. This study aimed to determine the effect and optimal dosage of golden apple snail POC on rubber seedling growth in peat media. The study was conducted from March to June 2024 at the Tempurukan Village experimental garden. The study used a non-factorial Completely Randomized Design (CRD) with 5 treatments and 4 replications. Each treatment consisted of 4 plants, resulting in 80 experimental units. Observation parameters included plant height (cm), number of umbrellas (stalks), stem diameter (cm), root length (cm), and plant dry weight (g). Data analysis used ANOVA and a 5% DMRT follow-up test using the DSAASTAT application. The results showed that golden apple snail POC application significantly affected plant height, stem diameter, number of umbrellas, root length, and dry weight of rubber plants. A dose of 40 golden apple snail POC per plant was the best treatment for increasing rubber seedling growth, with an average seedling height of 63.12 cm, stem diameter of 0.44 cm, number of parasols of 3, root length of 54.50 cm, and plant dry weight of 10.14 g.